Identity and Masculinity in Two Cases of Early-Onset Disability Autobiography - Pohjola, Hanna; Tarvainen, Merja (Narrative Works, 2019)
This article examines the construction of identity and masculinity in two cases of disability autobiography. Retrospectively written autobiographical accounts of early-onset disability were analyzed abductively by using the model of narrative circulation (MNC), with a thematic content analysis being used to organize the data. Both narrators constructed their adult identity as men in relation to the available disability narratives and living conditions. Three intertwined dimensions regarding the construction of identity could be observed: external expectations, internal intentions, and locally situated narratives of work. The narratives may be considered to represent an alternative way to bypass, overcome, and refresh the culturally dominant stock of stories.